CHARACTERISTIC STRENGTHS IN THE COMPRESSION AND IN THE STATIC BENDING AS PARAMETERS TO ESTIMATE CHARACTERISTIC SHEAR STRENGTH FOR TIMBER DESIGN - Almeida, João Paulo Boff; Wolenski, Anderson Renato Vobornik; Rodrigues, Edson Fernando Castanheira; de Araujo, Victor Almeida; Panzera, Túlio Hallak; de Campos, Cristiane Inácio [UNESP]; Molina, Julio Cesar; Christoforo, André Luis; Lahr, Francisco Antonio Rocco (FapUNIFESP (SciELO), 2023)
– To simplify the characterization of wood species, the Brazilian standard document ABNT NBR 7190-1 (2022) establishes the determination of mechanical properties employing the characteristic strength in the compression parallel to grain (fc0,k). This mechanical property is estimated using the linear relation given by the following expression fv0,k = 0.12·fc0,k . Brazilian and European standard documents support the estimation of fv0,k using relations among properties. However, the European guidelines in the EN 384 (2019) have used the conventional characteristic strength in the static bending test (fM,k). Thus, this study aimed to investigate the efficiency of the ratio fv0,k = 0.12·fc0,k for adopting 30 hardwoods. The variance analysis results demonstrate the divergence among the experimental outcomes and those values estimated using the relation cited. Therefore, regression models at two parameters were considered to obtain more accurate estimates of fv0,k by adopting fc0,k, and fM,k as independent variables. Regarding the results, the geometric (R2 = 80.80%) and linear (R² = 74.19%) models were the most accurate for the estimates of fv0,k in terms of fc0,k, and fM,k, respectively. This fact evinces the good accuracy of the models under consideration, which may provide a more rigorous structural design compared to the correlation currently prescribed by the ABNT NBR 7190-1 (2022).
RESISTÊNCIAS CARACTERÍSTICAS NA COMPRESSÃO E FLEXÃO ESTÁTICA COMO PARÂMETROS PARA A ESTIMATIVA DA RESISTÊNCIA CARACTERÍSTICA AO CISALHAMENTO NO PROJETO DE MADEIRA
Keywords: Brazilian hardwood; characteristic strengths; Shear strength estimates